2014
DOI: 10.2478/pjvs-2014-0094
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphism within LTF gene promoter with lactoferrin concentration in milk of Holstein cows

Abstract: This study analyzed the association between single nucleotide polymorphism (A/C) in position -28 located in the TATA box of LTF gene and the lactoferrin concentration in bovine milk secreted by healthy and infected udders. Out of 241, 69 cows were selected into the experimental group and were divided into 3 groups according to mean value of somatic cell count (SCC): I <180 000 cells/mL, II: 180 000 -350 000 cells/mL and III > 350 000 cells/mL. In each SCC group, three LTF genotypes: AA, AC and CC were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…Owing to the very low concentrations of LYZ and LTF in ruminants' milk, it is difficult to find literature data focused on the genetic background of their concentration variability. In a recently published paper, Zabolewicz et al described an association between the LTF gene −28A/C promoter variant and LTF amount in cattle milk. However, results presented in that study are not fully coherent, because the opposite direction of the relationship was noticed for cows affected and non‐affected with mastitis.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the very low concentrations of LYZ and LTF in ruminants' milk, it is difficult to find literature data focused on the genetic background of their concentration variability. In a recently published paper, Zabolewicz et al described an association between the LTF gene −28A/C promoter variant and LTF amount in cattle milk. However, results presented in that study are not fully coherent, because the opposite direction of the relationship was noticed for cows affected and non‐affected with mastitis.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar results were also reported by Li et al (2004) who characterized bovine lactoferrin gene including 5'flanking region using PCR-SSCP and then examined its association with subclinical mastitis, but the effects of different genotypes to somatic cell count (SCS), pre-SCS and primary SCS which are considered to be indicator traits for subclinical mastitis have not got the significant statistic. Zabolewicz et al (2014) have suggested significant association between SCC and Lf promoter genotype. To evaluate this association further in detail, a higher sample size could have been taken to reduce the sampling error.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic cell refers to PMN cells, macrophages and lymphocytes along with small percentage of epithelial cells (Concha 1986). Somatic cell count in cattle milk had been positively correlated with subclinical mastitis and to lactoferrin content (Huang et al 2010, Zabolewicz 2014 Lactoferrin gene is supposed to be a candidate gene for the mastitis-resistance trait (Seyfert et al 1996). Expression of bovine Lf mRNA is relatively low in the lactating gland but increases markedly during mammary gland infection (Molenaar et al 1996, Bruckmaier 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados de CCS vêm sendo correlacionados positivamente com mastites subclínicas e concentração de lactoferrina (HUANG et al, 2010;Zabolewicz et al, 2014;Chopra et al, 2015). De acordo com Chopra et al (2015), diferentes concentrações de LF são encontradas quando se comparam resultados de amostras de leite de vacas sadia com amostras de leite de vacas com mastite clínica e subclínica, sendo observado uma maior expressão genética do gene da LF em vacas com mastites.…”
Section: Avaliação Descritiva Por Escore De Células Somáticas E Proteínasunclassified